Exchange Rate Dynamics with Stock/Flow Interaction - Niehans, Jürg (Journal of Political Economy, 1977)
The paper examines the adjustment of the exchange rate and domestic prices to a monetary change under flexible exchange rates. The emphasis is on the dynamic interaction between the classical stock aspects, stressed by the monetary approach, and the flow aspects, stressed by the elasticity approach. It is shown that even in a very simple model of lagged asset adjustment the interaction between trade and capital flows can produce a large variety of adjustment paths, with and without overshooting, monotonic and cyclical.